Dampak digital terhadap Kesehatan Mental Remaja di SMA Bawakaraeng - Basmalah Harun; Magdalena Magdalena; Desi Ratnasari; Olivia (Universitas Muhammadiyah Manado, 2022)
Technology has developed rapidly, this is because technology has become a primary need for society. In our current digital era, we are witnessing changes in communication styles. However, the use of social media can have positive and negative impacts. Where the development of technology also has an impact on every aspect of life, including the psychology of every human being. Negative impacts include the mental health of teenagers. The aim of this activity is to increase teenagers' knowledge about the impact of digital on the mental health of teenagers at Bawakaraeng High School. The method used is lecture and discussion at the end of the meeting. The results of the activity show that it can increase teenagers' knowledge and that teenagers are willing to limit the use of social media, look for information other than social media, look for positive activities, use social media wisely, release and delete social media applications. Thus, the effect of using social media decreases on the mental health of its users.